Granulomatous Lesion of Breast: A Case Report - Agarwal, Ashna Ashish; Garg, Prem Kumar; Raina, Aditi; Agarwal, Ambika (Annals of Pathology and Laboratory Medicine, 2024)
A 25-year-old female presented with a complaint of a lump in the right breast, which was associated with mild pain. The patient also reported a past history of pulmonary tuberculosis, for which she had undergone treatment for six months. After obtaining consent from the patient, fine needle aspiration cytology, a minimally invasive procedure, was performed, leading to a diagnosis of granulomatous mastitis, which was confirmed by ancillary studies as breast tuberculosis. This is an uncommon clinical presentation of extrapulmonary tuberculosis. Histopathology, along with clinical history, remains the gold standard for the diagnosis of breast tuberculosis.